La reforma laboral “de los jóvenes” en Esp aña. Esp ecial referencia a la Ley 11/2013 y el rd-ley 16/2013 - Gonzáles Díaz, Francisco A. (2019)
The high rate of youth unemployment in Spain, surpassing the average of the countriesof the European Union, has forced a series of initiatives that were introduced in thedocument Entrepreneurship and Youth Employment Strategy. This article aims toapproach those measures with a legal-labor component, with particular reference toLaw 11/2013. This law articulates a series of measures through incentives to hiring,and its first result should lead to the reduction of youth unemployment. Thereforewe need to make reference to new contractual arrangements, to the reforms of thecurrent rules or to the recruitment incentives, which are linked to training activities.